KAJIAN SITASI KARYA ILMIAH DOSEN FIKOM UNPAD DALAM SKRIPSI MAHASISWA: ANALISIS SITASI KARYA ILMIAH DOSEN DALAM SKRIPSI MAHASISWA PADA DATABASE GDL DI FIKOM LIBRARY AND KNOWLEDGE CENTER (FLKC) UNIVERSITAS PADJADJARAN PADA SEMESTER GENAP TAHUN 2011 - Erwina, Wina; Sodikin, Yulianti (Universitas Pendidikan Indonesia, 2012)
This study aims to determine the citation analysis of scientific papers of undergraduate theses of students of the Faculty of Communication Sciences, University of Padjadjaran during the Even Semester of the Academic Year 2011. This study aims to determine the characteristics (shape, author / sources, language) which are frequently cited in scientific papers, publications of source of information, the frequency of citations of scientific papers and the development of Communication Information Science and Library Studies based on distribution subject of the cited references. The population studied is 227 titles of undergraduate theses from 4 departments (Journalism, Public Relations, Management Communication Library and Information Science). The population consists of 7089 citations. The results showed that the students appear to scientific papers from the Faculty of Communication’s lecturers. Especially those published in book form. The scientific papers of the Faculty of Communication’s lecturers are not yet cited in proper proportion. Besides that, there are students who still cite from private blogs. In general, student’s skill to cite is still below standard. The study recommended the socialization of scientific products of Faculty of Communication’s lecturers. A guide to standardization of bibliography writing is highly recommended.